Avaliação da produção de enzimas celulolíticas por fungos isolados da região dos Campos Gerais - Oliveira, Thais (2020)
Enzymes are natural catalysts of high biotechnological interest. These biocatalysts can be extracted from animal, vegetable and microorganism tissues, with microbial origin being the most used. There is a worldwide increase in the consumption of industrial enzymes and filamentous fungi are among the main microbial sources producing these enzymes. In this work, the enzymatic potential of fungi isolated from the soil of the region of Ponta Grossa - PR was evaluated, using wheat bran as a substrate. For this, 3 stages were carried out: fungi screening, fermentation in agitated flasks and fermentation in a bioreactor. The screening was carried out by inoculating the fungi in Petri dishes containing agar medium and supplemented with carboxymethylcellulose (CMC) incubated for 4 days at 32ºC. After the incubation period, the petri dishes were developed using the Congo Red 0.1% (w/v) dye, to verify the enzyme halo. Then the enzyme indexes (I.E) were determined. With this step, it was possible to select 3 fungi with the best enzyme indexes for the submerged fermentation step in agitated flasks. Submerged fermentation was carried out at 32 °C, pH 5.4 and stirring at 150 rpm. Fungi were evaluated for cellulose production. The CMIB-174 strain showed a higher enzymatic activity for both CMCase (0.032 IU/mL) and FPase (0.060 IU/mL). Therefore, the CMIB-174 strain was chosen for the bioreactor test. It can be observed that the bioreactor assay favored the activities of CMCase and FPase with a significant increase of 433% and 146%, respectively. However, all strains used in the present study showed low enzymatic activities when compared to other results obtained in the literature.